Pengembangan Media Komik pada Pembelajaran IPA - Nurul Khairunnisa; Leo Charli; Elya Rosalina (Journal of Elementary School (JOES), 2023)
This study aims to produce science learning media comic in Class V B SD Negeri 55 Lubuklinggau on theme 6 Sub-Theme 2 Heat Transfer around Us which is valid and practical. The development model or Research and Development (R&D) carried out in this study is to use the 4-D development model. The research instrument was in the form of validation sheets from material experts, linguists and media experts. The data collection tool uses a questionnaire to obtain data on product eligibility through validation questionnaires and practicality questionnaires for teachers and students. With a small group test sample of 9 students with different cognitive levels, the teacher's practicality test was then carried out. Based on the results of research and data analysis on the use of comic media, it was found that the validity test by the three experts showed that comic media met the Aiken's V validation interpretation criteria of 0.82 with high validation criteria. While the practicality test of teachers and students obtained student practicality of 94% in the very practical category and the teacher's practicality test of 75% in the practical category with a total of 85% in the very practical category. So it can be concluded that comic media meets valid and practical criteria and can be used in the process of teaching and learning activities. Keywords: 4-D Development Model, Comic Media, Science Learning